1998
DOI: 10.1016/s0378-1097(98)00166-9
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen depletion induced dormancy in Mycobacterium smegmatis

Abstract: We report here that the physiological behaviour of the fastgrowing saprophytic Mycobacterium smegmatis under in vitro oxygen-depletion and reactivation conditions is strikingly similar to the characteristics shown by the slowgrowing pathogenic M. tuberculosis. M. smegmatis died rapidly when shifted abruptly from aerobic to anaerobic conditions. In contrast to the lethal shock of abrupt oxygen depletion, the slow depletion through a selfgenerated oxygen gradient permitted an adaptation to a persistent state whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
112
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(115 citation statements)
references
References 10 publications
2
112
0
1
Order By: Relevance
“…M. smegmatis strains were grown to an OD 600 of 0.5-0.6 (~1.5-2.0610 8 c.f.u. ml 21 ) in Dubos medium with 10 % ADC and diluted 1 : 100 in triplicate in screw-cap flat-bottom culture tubes containing 20 ml of the same medium and 10 ml of air space (headspace ratio 0.5; Dick et al, 1998). The tubes were sealed and the cultures were grown with slow stirring using a multipoint magnetic board at 37 uC for 10 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…M. smegmatis strains were grown to an OD 600 of 0.5-0.6 (~1.5-2.0610 8 c.f.u. ml 21 ) in Dubos medium with 10 % ADC and diluted 1 : 100 in triplicate in screw-cap flat-bottom culture tubes containing 20 ml of the same medium and 10 ml of air space (headspace ratio 0.5; Dick et al, 1998). The tubes were sealed and the cultures were grown with slow stirring using a multipoint magnetic board at 37 uC for 10 days.…”
Section: Methodsmentioning
confidence: 99%
“…Wayne has defined in vitro growth conditions to mimic hypoxia using sealed culture tubes with a defined empty space above the medium (Wayne & Lin, 1982;Wayne & Hayes, 1996). Earlier reports (Dick et al, 1998;Mayuri et al, 2002) have described adaptation of these growth conditions for M. smegmatis and shown that several physiological changes that the bacterium undergoes during such a growth are common to those encountered by M. tuberculosis under the same conditions. Considering that hypoxic conditions are known to induce DNA damage (Moller et al, 2001;Grishko et al, 2001) it was of interest to subject the various DNA-repair-deficient M. smegmatis strains to the hypoxic growth model of Wayne.…”
Section: Effect Of Acidified Sodium Nitrite On the Growth Of M Smegmmentioning
confidence: 98%
“…Adaptation to transient and prolonged oxygen deprivation has been demonstrated in both saprophytic mycobacteria (e.g., M. smegmatis) and pathogenic species (e.g., M. tuberculosis) (7,8). M. tuberculosis uses anaerobic electron sinks such as nitrate and possibly fumarate (9,10).…”
mentioning
confidence: 99%
“…This will be greatly facilitated by a better understanding of the physiological state of these latent bacteria. Although several in vitro models suggest low extracellular concentrations of oxygen to be an important cause for mycobacterial dormancy (8,10,42), the effect of this state on cellular metabolism is not clear.It has been shown that the morphology and staining pattern of an in vitro culture of mycobacteria differ from those of persistors which are obtained from the lung lesion and are chromophobic to the conventional acid-fast staining (25, 26). The former is an acid-fast and long rod-shaped bacillus, as opposed to the latter, which is non-acid fast and granular.…”
mentioning
confidence: 99%
“…This will be greatly facilitated by a better understanding of the physiological state of these latent bacteria. Although several in vitro models suggest low extracellular concentrations of oxygen to be an important cause for mycobacterial dormancy (8,10,42), the effect of this state on cellular metabolism is not clear.…”
mentioning
confidence: 99%